2020
DOI: 10.1186/s12887-020-1926-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in treatments and interventions received by children and adolescents with cerebral palsy

Abstract: Background: In the Swedish population-based follow-up program and national quality registry for individuals with cerebral palsy (CPUP), physiotherapy (PT) and occupational therapy (OT) treatments are regularly recorded along with functional status. By Swedish law, all citizens irrespective of personal characteristics or socioeconomic status, have the right to receive healthcare and medical treatments as applicable. Previous research has shown gender differences in treatments and interventions received by child… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Girls were less likely to have undergone surgery (selective dorsal rhizotomy) or intrathecal baclofen and they were more likely to have spinal braces (Josenby, 2020) maybe because female sex is more associated with the risk of scoliosis (Pettersson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Girls were less likely to have undergone surgery (selective dorsal rhizotomy) or intrathecal baclofen and they were more likely to have spinal braces (Josenby, 2020) maybe because female sex is more associated with the risk of scoliosis (Pettersson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Eleven articles related sex to the different kind of interventions or outcomes in a rehabilitation program (Brunton & Bartlett, 2010; Degerstedt et al, 2017; Engel‐Yeger et al, 2009; Feitosa et al, 2017; Franzén et al, 2017; Gough et al, 2008; Himmelmann et al, 2020; Josenby, 2020; Mitchell et al, 2015; Wolter et al, 2020; Zwick et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on spasticity reducing methods in Sweden have reported sex differences. A Swedish population-based study showed that significantly more boys than girls were treated with SDR [ 18 ]. In another Swedish population-based study based on treatments reported 2014–2015, significantly more boys received BTX-A [ 18 ].…”
Section: Spasticity Treatments By Sex and Countrymentioning
confidence: 99%
“…A Swedish population-based study showed that significantly more boys than girls were treated with SDR [ 18 ]. In another Swedish population-based study based on treatments reported 2014–2015, significantly more boys received BTX-A [ 18 ]. However, this difference was not found in reports from 2016–2017 [ 19 ], or in the present study.…”
Section: Spasticity Treatments By Sex and Countrymentioning
confidence: 99%